(untitled) (Asian Journal of Medical and Biological Research, 2017)
Tenascin-C, an extracellular matrix glycoprotein, expresses high level during embryogenesis and almost absent during the normal postnatal life. However, it is re-appeared in a diverse condition such as tissue injury and in the stroma of various carcinomas. In this study, we investigated the appearance of tenascin-C in dextran sulfate sodium (DSS)-induced colitis in mice. DSS induced colitis mice demonstrated severe mucosal damage, with distortion and loss of crypts, depletion of goblet cells and infiltration of macrophages particularly F4/80 positive macrophages, granulocytes and lymphocytes in the colon tissues. These DSS inflamed colon expressed a high and dense level of tenascin-C in the severe damaged areas, whereas, moderate staining was observed in the moderate inflamed areas. DSS-induced colitis mice significantly increased macrophages infiltration in the colon tissues. These results suggested that tenascin-C extracellular matrix re-appeared in the colon tissues during inflammation. Asian J. Med. Biol. Res. December 2016, 2(4): 582-586